2020
DOI: 10.21580/jec.2020.2.2.6318
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Chemophobia dan faktor yang mempengaruhi Persepsi pada Mahasiswa

Abstract: <p>“<em>Chemophobia</em>” atau kecemasan kimia diyakini menjadi salah satu penyebab sedikitnya minat siswa terhadap jurusan kimia. Siswa juga kurang optimal dalam memahami pelajaran kimia. Siswa memandang kimia sebagai sesuatu yang negatif yang disebabkan oleh persepsi dan informasi yang mengenai kimia. Jenis penelitian ini adalah penelitian deskriptif dengan menggunakan pendekatan kualitatif. Penelitian ini bertujuan untuk mengidentifikasi eksistensi <em>Chemophobia</em>  di kala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In line with the theory of Lee et al (2019) which says that unfounded fear of chemicals caused by a lack of comprehensive knowledge and information. Herlina et al (2020) also said that the more one understands or has more knowledge of an object, the better that person's view of the object will be.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with the theory of Lee et al (2019) which says that unfounded fear of chemicals caused by a lack of comprehensive knowledge and information. Herlina et al (2020) also said that the more one understands or has more knowledge of an object, the better that person's view of the object will be.…”
Section: Resultsmentioning
confidence: 99%
“…Including in Indonesia, as research conducted by Hamid (2018) on people in the Yogyakarta area found chemophobia. Chemophobia is even still found in students, as research has been done by Herlina et al (2020) should Chemophobia no longer be identified, considering that the respondent's background is already at the student level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation